DNA barcoding of marine fishes from Saudi Arabian waters of the Gulf. Issue 5 (25th October 2019) - Rabaoui, Lotfi; Yacoubi, Lamia; Sanna, Daria; Casu, Marco; Scarpa, Fabio; Lin, Yu‐Jia; Shen, Kang‐Ning; Clardy, Todd R.; Arculeo, Marco; Qurban, Mohammad A.
Abstract: We used the cytochrome oxidase subunit I ( coI ) gene DNA to barcode 117 endemic Gulf and cosmopolitan Indo–West Pacific fish species belonging to 54 families and 13 orders. Novel DNA barcodes were provided for 18 fish species ( Trachinocephalus sp., Nematalosa sp., Herklotsichthys lossei, Upeneus doriae, Trachurus indicus, Apogonichthyoides taeniatus, Verulux cypselurus, Favonigobius sp., Suezichthus gracilis, Sillago sp., Brachirus orientalis, Pegusa sp., Lepidotrigla bispinosa, Lepidotrigla sp., Grammoplites suppositus, Hippichthys sp., Paramonacanthus sp. and Triacanthus sp.). The species delimitation analysis, conducted with Poisson tree processes– Bayesian PTP (PTP–bPTP) and nucleotide‐divergence‐threshold (NDT) models), found 137 and 119 entities respectively. Overall, NDT method, neighbour‐joining species tree and the prior taxonomic assessment provided similar results. Among the 54 families considered, only 10 (Ariommatidae, Ephippidae, Leiognathidae, Nemipteridae, Plotosidae, Pomacanthidae, Pomacentridae, Priacanthidae and Rachycentridae) showed the occurrence of molecular diagnostic pure characters. The DNA barcoding database developed during this study will help ichthyologists to identify and resolve the taxonomic ambiguities they may encounter with the fishes occurring in The Gulf and throughout the region.